Piranska notarska knjiga (Zvezek 3) = The Notary Book from Piran (Vol. 3) Fragmenti (1289-1292) = Fragments (1289-1292) - Mihelič, Darja (Thesaurus memoriae, 2002)
The third volume of The Notary Book from Piran is a scientific issue of the source - the book of the notary Sclavion with imbreviations of 589 documents of various contents, which is kept at the Piran Archives. It contains the transcription of the original Latin text, notes, an index of personal and place names, a factual register, and a list of summaries of entries.